Hybrid repair of early aortobifemoral graft occlusion in a patient with antiphospholipid syndrome: A case report: Hybrid repair of graft occlusion in APS - Vermylen, Laurens; Daenen, Geert; Stabel, Patrick; Avet, Jo; Peeters, Karen (Journal of Surgery and Medicine, 2026)
Complete thrombosis of an aortic segment and unilateral graft limb after aortobifemoral bypass is a rare but severe complication. We report the case of a 41-year-old female patient who presented 2.5 months after aortobifemoral bypass for Leriche syndrome with recurrent claudication and ischemic rest pain. Imaging revealed complete thrombosis of the proximal aortic segment and the right iliac graft limb. A hybrid repair was performed consisting of bilateral groin incisions, thrombectomy, endarterectomy, and placement of kissing covered stents. Postoperative recovery was uneventful, with restored perfusion and good graft patency on follow-up. Thrombophilia screening demonstrated antiphospholipid syndrome, which was considered an important contributor to the early graft failure. This case illustrates that hybrid repair can be a safe and effective option for early aortobifemoral graft occlusion and highlights the importance of systemic evaluation for prothrombotic disorders in young patients presenting with unexplained thrombosis.